-7m+13+8m-5=

Simple and best practice solution for -7m+13+8m-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7m+13+8m-5= equation:


Simplifying
-7m + 13 + 8m + -5 = 0

Reorder the terms:
13 + -5 + -7m + 8m = 0

Combine like terms: 13 + -5 = 8
8 + -7m + 8m = 0

Combine like terms: -7m + 8m = 1m
8 + 1m = 0

Solving
8 + 1m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 1m = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 1m = 0 + -8
1m = 0 + -8

Combine like terms: 0 + -8 = -8
1m = -8

Divide each side by '1'.
m = -8

Simplifying
m = -8

See similar equations:

| 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 | | x-14.6=20 | | 5(k+2)=3(-4) | | -8m+15+9m-2= | | Y=-10(5)-3 | | n+221=333 | | 5m-13=33 | | 9x^4=3x^2-25 | | 5(5x)+12= | | 5(5x+12)= | | 4n+24=2n+42 | | 3p+5=2p+14 | | 2(13.5)+-1.5y+3y=27 | | 2*2*n*n=54 | | 12x=3x+12 | | 23xn=22135 | | 2(13.5+-1.5y)+3y=27 | | 5(y-3)+2(y+4)=42 | | 18x+6=3x+18 | | 13(12x+15)=7 | | -7y+5(y-4)=-10 |

Equations solver categories